2011
DOI: 10.1002/chem.201100608
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Mechanistic Study of Facile CO Bond Formation between a Well‐Defined Aryl–Copper(III) Complex and Oxygen Nucleophiles

Abstract: A well-defined macrocyclic aryl–Cu(III) complex (2) reacts readily with a variety of oxygen nucleophiles, including carboxylic acids, phenols and alcohols, under mild conditions to form the corresponding aryl esters, biaryl ethers and alkyl aryl ethers. The relationship between these reactions and catalytic C-O coupling methods is demonstrated by the reaction of the macrocyclic aryl–Br species with acetic acid and p-fluorophenol in the presence of 10 mol% Cu(I). An aryl-Cu(III)-Br species 2(Br) was observed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 42 publications
2
78
0
5
Order By: Relevance
“…Once 1 ClO4 was fully characterized, we turned our attention towards its reactivity. We speculated that this complex could show a similar reactivity to its analogous copper complex, that is, to undergo reductive eliminations to functionalize the C sp2 -M(III) (M ¼ Cu or Ag) bond in the presence of nucleophiles of different nature 19,35 . The reaction of 1 ClO4 with sulfonamides, aromatic and aliphatic carboxylic acids, phenols and thiophenols resulted in the formation of C arylnucleophile coupling products in excellent yields, characteristic of a reductive elimination reaction (products 2a-2g, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Once 1 ClO4 was fully characterized, we turned our attention towards its reactivity. We speculated that this complex could show a similar reactivity to its analogous copper complex, that is, to undergo reductive eliminations to functionalize the C sp2 -M(III) (M ¼ Cu or Ag) bond in the presence of nucleophiles of different nature 19,35 . The reaction of 1 ClO4 with sulfonamides, aromatic and aliphatic carboxylic acids, phenols and thiophenols resulted in the formation of C arylnucleophile coupling products in excellent yields, characteristic of a reductive elimination reaction (products 2a-2g, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Later in 2010, Ribas and Stahl's groups demonstrated that the final C-N coupling products could be achieved in a catalytic fashion by employing [Cu I (CH 3 CN) 4 ] PF 6 as catalyst (<5 mol%) and the macrocyclic aryl bromide 19e-Br as substrate via aryl-Cu III -Br intermediates [39]. The same operative Cu I /Cu III catalytic cycle has been now validated for O-, S-, Se-, and P-nucleophiles (Scheme 16) [52,55].…”
Section: Mechanistic Insights On Ullmann-type Coupling Reactionsmentioning
confidence: 93%
“…Our research group and others have demonstrated the capability of aryl-Cu III complexes to generate C aryl -heteroatom bonds upon reaction with nitrogen-based nucleophiles [41] (lactams, imides, sulfonamides, oxazolidone, and benzamides), oxygen-based nucleophiles [45,[52][53][54] (carboxylic acids, alcohols), sulfur-based nucleophiles [45,55] (thiols, thiocyanate), selenium-based nucleophiles [55] (benzeneselenol), and phosphorus-based nucleophiles [55] (H-phosphonate diesters). This step can be envisioned to occur through two possible mechanisms:…”
Section: Mechanistic Insights On Ullmann-type Coupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the evidence collected so far has shown that the active catalyst is a ligand-copper(I)-nucleophile [(L)Cu I (Nu)] species, there is no such agreement on the way this catalyst activates the aryl halide (ArY, Y = Cl, Br and I). The most invoked routes are based on either one-electron redox processes through the radical intermediate Cu I /Cu II catalytic cycle namely Single Electron Transfer (SET) and Halogen Atom Transfer (HAT) [4,[39][40][41][42], or on two-electron redox processes via a Cu I /Cu III catalytic cycle like Oxidative Addition-Reductive Elimination (OA-RE) or σ-bond Metathesis (MET) (Scheme 1) [37,38,[43][44][45][46][47][48][49][50]. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%